HeLa-CCL2 cell heterogeneity studied by single-cell DNA and RNA sequencing. - Wan-Er Hu; Xin Zhang; Qiu-Fang Guo; Jing-Wei Yang; Yuan Yang; Shi-Cheng Wei; Xiao-Dong Su (PLoS ONE, 2019)
The HeLa cells are the earliest and mostly used laboratory human cells for biomedical particularly cancer research. They were derived from a patient's cervical cancerous tissue, and are known for their heterogeneous cellular origin and variable genomic landscapes. Single-cell sequencing techniques with faithful linear and uniformly amplified genomes (DNA) and transcriptomes (RNA) may facilitate the study of cellular differences at the individual cell level. In this work, we have performed single-cell DNA and RNA sequencing with HeLa-CCL2 cells to study their heterogeneity. We have studied the complexity of copy number variations (CNVs) of HeLa-CCL2 genome at the single cell level, and revealed the transcriptomic heterogeneity of HeLa-CCL2. We also analyzed the relationship between genome and transcriptome at the single-cell level, and found overall correlation between CNV and transcriptome expression patterns. Finally, we concluded that although single-cell sequencing techniques are applicable to study heterogeneous cells such as HeLa-CCL2, the data analyses need to be more careful and well controlled.